Targeted delivery of a proapoptotic peptide to tumors in vivo - Dufort, Sandrine (Informa Healthcare, 2011)
RGD peptides recognize the α(v)β(3) integrin, a receptor that is overexpressed on the surface of both tumour blood vessels and cancerous cells. These peptides are powerful tools that act as single antiangiogenic molecules, but recently also have been used for tumour imaging and drug targeting. We designed the molecule RAFT-(c[-RGDfK-])(4), a constrained and chemically defined entity that can be produced at clinical grade quality. This scaffold was covalently coupled via a labile bridge to the proapoptotic peptide (KLAKLAK)(2) (RAFT-RGD-KLA). A fluorescent, activatable probe was also introduced, allowing intracellular localization. At 2.5 μM, this molecule induced the intracellular release of an active KLA peptide, which in turn caused mitochondrial depolarization and cell death in vitro in tumour cells. In a mouse model, the RAFT-RGD-KLA peptide was found to prevent the growth of remote subcutaneous tumours. This study demonstrated that the antitumour peptide is capable of killing tumour cells in an RGD-dependent manner, thus lowering the non-specific cytotoxic effects expected to occur when using cationic cytotoxic peptides. Thus, this chemistry is suitable for the design of complex, multifunctional molecules that can be used for both imaging and therapeutics, representing the next generation of perfectly controlled, targeted drug delivery systems.